Leaning-based interfaces improve ground-based VR locomotion in reach-the-target, follow-the-path, and racing tasks - Hashemian, Abraham M.; Adhikari, Ashu; Kruijff, Ernst; Heyde, Markus von der; Riecke, Bernhard E. (IEEE Transaction on visualization and computer graphics TVCG, 2021)
Using standard handheld interfaces for VR locomotion may not provide a believable self-motion experience and can contribute to unwanted side effects such as motion sickness, disorientation, or increased cognitive load. This paper demonstrates how using a seated leaning-based locomotion interface –HeadJoystick– in VR ground-based navigation affects user experience, usability, and performance. In three within-subject studies, we compared controller (touchpad/thumbstick) with a more embodied interface (”HeadJoystick”) where users moved their head and/or leaned in the direction of desired locomotion. In both conditions, users sat on a regular office chair and used it to control virtual rotations. In the first study, 24 participants used HeadJoystick versus Controller in three complementary tasks including reach-the-target, follow-the-path, and racing (dynamic obstacle avoidance). In the second study, 18 participants repeatedly used HeadJoystick versus Controller (8 one-minute trials each) in a reach-the-target task. To evaluate potential benefits of different brake mechanisms, in the third study 18 participants were asked to stop within each target area for one second. All three studies consistently showed advantages of HeadJoystick over Controller: we observed improved performance in all tasks, as well as higher user ratings for enjoyment, spatial presence, immersion, vection intensity, usability, ease of learning, ease of use, and rated potential for daily and long-term use, while reducing motion sickness and task load. Overall, our results suggest that leaning-based interfaces such as HeadJoystick provide an interesting and more embodied alternative to handheld interfaces in driving, reach-the-target, and follow-the-path tasks, and potentially a wider range of scenarios.
Keywords: NSERC DG 2026; Riecke; Riecke_2021; abraham-hashemian; ashu-adhikari; bernhard-riecke; ernst-kruijff; journalPaper; markus-von-der-heyde; motion-cueing; proj--headjoystick-2d; proj--motionCueingInterfaces